Program Literasi Islami untuk Menumbuhkan Karakter Religius pada Anak Usia Dini, Studi Pengembangan di Kelurahan Timbang Langkat, Binjai Timur - Rizka Auliah Hasibuan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Islamic Literacy Program to Foster Religious Character in Early Childhood is a community service initiative aimed at instilling Islamic values through engaging and meaningful literacy activities. The program was conducted for two weeks in Timbang Langkat Village, Binjai Timur District, involving early childhood learners, PAUD teachers, and parents. This study employed a Participatory Action Research (PAR) approach consisting of planning, action, observation, and reflection stages. Data were collected through observation, interviews, and documentation, then analyzed descriptively using the Miles and Huberman interactive model. The findings showed a 31% average increase in children’s religious character aspects, including faith, discipline, honesty, responsibility, and social attitude. Furthermore, teacher and parent involvement played a crucial role in strengthening the internalization of religious values through enjoyable literacy activities such as storytelling of prophets, writing Arabic letters, and Islamic role-playing. The implications indicate that Islamic literacy effectively fosters religious character development in early childhood in a contextual and sustainable manner and can serve as a model for other PAUD institutions in developing Islamic character education programs.